Conditioned Medium from Cultured Colorectal Cancer Cells Affects Peripheral Blood Mononuclear Cells Inflammatory Phenotype in Vitro - Bahareh Mohebbi; Kaveh Ashtibaghaei; Mehrdad Hashemi; Mahmoud Hashemi; Hamid Asadzadeh Aghdaei; Mohammad Reza Zali (Iranian Journal of Medical Sciences, 2019)
Background: Colorectal cancer (CRC) is the third most common cancer worldwide. Studies have indicated that immune cells and soluble factors play a key role in maintaining the balance between tumor-promoting inflammation and anti-tumor immunity. It has been shown that secreted cytokines from CRC cell lines could affect peripheral blood mononuclear cells (PBMCs), monocytes, and macrophages phenotypes. Macrophage infiltration has been associated with good prognosis in some cancers, but with poor prognosis in others. The present study aimed to evaluate the effect of conditioned media from CRC cells (Caco-2) on immune responses produced by PBMCs. Methods: The present study was performed at the Gastroenterology and Liver Diseases Research Institute, Shahid Beheshti University of Medical Sciences (Tehran, Iran) in 2017. Human monocytes were isolated from PBMCs by Ficoll gradient media. The co-culture of monocytes and Caco-2 conditioned media was carried out. RNA extraction and cDNA synthesis of monocytes were performed after 96 hours. Gene expression of pro- and anti-inflammatory cytokines was evaluated by real-time PCR. Statistical analysis was performed using the SPSS software (version 21.0) with the independent sample t test. P